2023
DOI: 10.1007/s10705-023-10264-2
|View full text |Cite
|
Sign up to set email alerts
|

Developing a nitrogen fertilizer management model for wheat in calcareous soils using the critical nitrogen dilution curve

Abstract: The critical nitrogen (N) dilution curve, which expresses whole-plant critical N concentration as a function of shoot biomass, can be used as a N management diagnostic tool for cereals. The objectives of this research were to develop a critical N dilution curve for wheat grown in calcareous soils and to formulate a model for estimating N fertilizer requirement of wheat crop at different growth stages. Six N fertilization rates (0–250 kg N ha−1) were used to induce variability in plant growth throughout six sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Since soil pH is presumed to be a key factor influencing the sorption of P, poultry manure may have lower P adsorption in calcareous soils. In calcareous soils, Ca build-up can result in CaCO3 precipitating surrounding roots (Ali, Saudi, & El-Sadek, 2023), which can stunt plant growth by causing chlorosis due to lime. In contrast with poultry manure, the findings of this study have also shown that the combination of biochar and mycorrhiza, particularly Cattle1 t.h.…”
Section: Biochars Level and Mychorhyzamentioning
confidence: 99%
See 1 more Smart Citation
“…Since soil pH is presumed to be a key factor influencing the sorption of P, poultry manure may have lower P adsorption in calcareous soils. In calcareous soils, Ca build-up can result in CaCO3 precipitating surrounding roots (Ali, Saudi, & El-Sadek, 2023), which can stunt plant growth by causing chlorosis due to lime. In contrast with poultry manure, the findings of this study have also shown that the combination of biochar and mycorrhiza, particularly Cattle1 t.h.…”
Section: Biochars Level and Mychorhyzamentioning
confidence: 99%
“…Biochar and its impact on soils can lessen the requirement for synthetic fertilizers. It has been demonstrated that biochar, which depends on its porosity and surface charge, enhances the soil's ability to retain nutrients in calcareous soil (Ali, Saudi, & El-Sadek, 2023). Biochar improves soil nitrogen and phosphorus retention by minimizing leaching and gaseous loss, depending on the pyrolysis and feedstock conditions.…”
Section: Introductionmentioning
confidence: 99%